Oral and gastric helicobacter pylori : Effects and associations - Veiga, Nélio (2016)
This study consisted in the comparison of the prevalence of Helicobacter pylori (H. pylori) present in the stomach and in saliva of a sample of Portuguese adolescents and the assessment of the association between H. pylori infection with socio-demographic variables and prevalence of dental caries.